Jallad : Death Squads and State Terror in South Asia - Tasneem Khalil (London Pluto Press, 2016)
The story of South Asian death squads is the story of rampant state terror. From Balochistan in Pakistan to Barisal in Bangladesh, military and paramilitary forces roam the streets under different names and in different formations. However, they carry the same toolbox of abuse: torture, rape, enforced disappearances and cold-blooded executions. These are units which are recognized and protected by the state - acting as part of regular security forces, shielded by black laws or emergency acts. Khalil argues that the existence of death squads and a politics of extrajudicial executions are symptoms of socio-political conditions. These abuses occur in weak postcolonial states that often lack the consent of the ruled. Militarism remains the dominant doctrine in policy making and statecraft. And hegemonic foreign sponsorship of the ruling elite impedes the establishment of democratic order. This book sets out to close a gap in the literature on human rights in South Asia, in which socio-political analysis of state terror is hard to come by. Khalil unveils the bloody logic of domination and repression that lies at the very core of statecraft in South Asia.
Include Notes and Index.
Death Squads and State Terror in South Asia.
Keywords: Political atrocities -- State-sponsored terrorism -- South Asia